Eusebi Colomer and the Philosophy of History - Monserrat Molas, Josep (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This article intends to show that Eusebi Colomer also dedicated a special attention to the question of history. For Colomer, the philosophies of history have been erroneous, and the question that originates from them can only be resolved in the theology of history. What the main source of this conception is and how Colomer would change it radically are also presented. An approximation of Colomer’s thought is given in this work, whose objective is to show that Eusebi Colomer paid a special attention to history as object of reflection.
Keywords: Eusebi Colomer; philosophy of history; theology of history